Bentuk, Fungsi, dan Makna Upacara Manenung di Desa Tumbang Baringei Kecamatan Rungan Kabupaten Gunung Mas - I Wayan Sindia Griya Danika; Yoga Yoga; Nurlensi Nurlensi (Widya Katambung, 2025)
This study aims to describe the form, function, and meaning of the Manenung ceremony in the Hindu Kaharingan community of Tumbang Baringei Village, Rungan District, Gunung Mas Regency. The research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. Informants consisted of three Basir/Pisor (spiritual leaders) and two Hindu Kaharingan religious figures. Data were analyzed using the Miles and Huberman interactive model involving reduction, presentation, and conclusion drawing. The findings reveal that the Manenung ceremony is performed through preparatory stages, chanting of sacred mantras, and the invocation of the holy spirit Putir Santang. The ceremony functions religiously as a means of spiritual communication, socially as a medium of community solidarity, and educationally as a vehicle for transmitting cultural values. The symbolic meanings embedded in ritual instruments such as amak purun, baliung, tengang, and behas tawur reflect cosmic harmony between humans, nature, and the divine. This tradition remains relevant in preserving the cultural identity and spirituality of the Dayak Kaharingan community amid modernization, serving as a vital source of moral guidance and local wisdom.